Changes in Index of Microcirculatory Resistance during PCI in the Left Anterior Descending Coronary Artery in Relation to Total Length of Implanted Stents. (1st December 2019) - Ekenbäck, Christina; Jokhaji, Fadi; Östlund-Papadogeorgos, Nikolaos; Mir-Akbari, Habib; Linder, Rikard; Witt, Nils; Törnerud, Mattias; Samad, Bassem; Persson, Jonas
Abstract : Aim . To investigate the relationship between stent length and changes in microvascular resistance during PCI in stable coronary artery disease (CAD). Methods and Results . We measured fractional flow reserve (FFR), index of microcirculatory resistance (IMR), and coronary flow reserve (CFR) before and after stenting in 42 consecutive subjects with stable coronary artery undergoing PCI with stent in the LAD. Patients that had very long stent length (38–78 mm) had lower FFR before stenting than patients that had long (23–37 mm) and moderate (12–22 mm) stent length (0.59 (±0.16), 0.70 (±0.12), and 0.75 (±0.07); p = 0.002 ). FFR improved after stenting and more so in subjects with very long stent length compared to long and moderate stent length (0.27 (s.d ± 16), 0.15 (s.d ± 0.12), and 0.12 (s.d ± 0.07); p for interaction = 0.013). Corrected IMR (IMRcorr ) increased after stenting in subjects who had very long stent length, whereas IMRcorr was lower after stenting in subjects who had long or moderate stent length (4.6 (s.d. ± 10.7), −1.4 (s.d. ± 9, 9), and −4.2 (s.d. ± 7.8); p for interaction = 0.009). Conclusions . Changes in IMR during PCI in the LAD in stable CAD seem to be related to total length of stents implanted, possibly influencing post-PCI FFR. Larger studies are needed to confirm the relationship.